Multi-Country Report : Ensuring Financial Stability in Countries with Islamic Banking-Case Studies-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This paper presents country experiences with reforms to strengthen regulatory oversight of the Islamic banking sector. Based on the selected country experiences, a number of important lessons and policy options can be drawn that have implications for the stable and sound development of Islamic banking. An enabling regulatory and institutional framework and a level playing field for conventional and Islamic banks is critical for the sound and stable growth of the Islamic banking industry. The country experiences also underscore the importance of providing an enabling framework while letting market forces determine the size of the industry.